Role of AMH in Prediction of Menopause - de Kat, Annelien C.; Broekmans, Frank J. M.; Lambalk, Cornelis B. (Frontiers in Endocrinology, 2021)
Anti-Müllerian Hormone (AMH) is produced by small antral follicles and has evolved over the past three decades as an assumed potential marker of the number of follicles in the human ovaries, also known as ovarian reserve. This quantitative measure, given the gradual decline over time and its non-replenishable feature, could be the dreamed marker for predicting the final exhaustion of ovarian storage: the post-menopause. This introductory chapter summarizes current knowledge with regard to the contribution of serum AMH measurements to predict age of normal menopause in assumed normal women and critically discuss its potential in this regard. Furthermore, its predictive role in the context of menopause in association with several frequently occurring fertility disorders such as premature menopause, polycystic ovarian syndrome and endometriosis are discussed. Overall, while ovarian reserve markers including AMH are unmistakably related to age at menopause, they are insufficiently precise to inform on an individual’s journey of ovarian aging.